2019
DOI: 10.1002/jcp.28060
|View full text |Cite
|
Sign up to set email alerts
|

H19 and Foxc2 synergistically promotes osteogenic differentiation of BMSCs via Wnt‐β‐catenin pathway

Abstract: Objective To investigate the mechanism of H19 on the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Methods Ovariectomized (OVX) mouse model was established. RNA immunoprecipitation and RNA pull‐down assays were performed to determine the correlation between H19 and forkhead box C2 (Foxc2). Chromatin immunoprecipitation assay was used to identify whether Foxc2 binds to the Wnt4 promoter region. Molecules expressions were measured by quantitative real‐time polymerase chain reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
(40 reference statements)
2
26
0
Order By: Relevance
“…It has been found that H19 downregulation modulated osteogenic differentiation of BMSCs from ovariectomized mouse, which suggested an important role of H19 in postmenopausal osteoporosis [26]. In the present study, we observed a significant decrease of H19 expression in postmenopausal osteoporosis patients and in BMP-2 induced BMSCs compared with controls, which was consistent with a former study [26]. And more importantly, our results indicated that H19 overexpression downregulated miR-19b-3p expression in BMSCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been found that H19 downregulation modulated osteogenic differentiation of BMSCs from ovariectomized mouse, which suggested an important role of H19 in postmenopausal osteoporosis [26]. In the present study, we observed a significant decrease of H19 expression in postmenopausal osteoporosis patients and in BMP-2 induced BMSCs compared with controls, which was consistent with a former study [26]. And more importantly, our results indicated that H19 overexpression downregulated miR-19b-3p expression in BMSCs.…”
Section: Discussionsupporting
confidence: 92%
“…LncRNA H19 has been addressed in various cancers as an oncogene, and regulated cell proliferation, apoptosis and migration [25]. It has been found that H19 downregulation modulated osteogenic differentiation of BMSCs from ovariectomized mouse, which suggested an important role of H19 in postmenopausal osteoporosis [26]. In the present study, we observed a significant decrease of H19 expression in postmenopausal osteoporosis patients and in BMP-2 induced BMSCs compared with controls, which was consistent with a former study [26].…”
Section: Discussionsupporting
confidence: 92%
“…Although Morusin has the ability to effectively advance osteogenic differentiation of BMSCs, its underlying mechanism remains unclear. As confirmed by previous studies, Wnt/β-catenin signaling pathway is a great mediator of BMSCs differentiation into osteoblasts [37][38][39]. Therefore, we studied the function of Wnt/β-catenin signaling pathway in the osteogenesis of BMSCs treated by Morusin.…”
Section: Discussionmentioning
confidence: 52%
“…Among LncRNAs, H19 has been addressed in various cancers as an oncogene, and regulated cell proliferation, apoptosis and migration [64]. It has been found that H19 down-regulation modulated osteogenic differentiation of BMSCs from ovariectomized mouse, which suggested an important role of H19 in postmenopausal osteoporosis [65]. LncRNA H19 also mediates mechanical tension-induced osteogenesis of BMMSCs via FAK by sponging miR-138 [32].…”
Section: Discussionmentioning
confidence: 99%